2020
DOI: 10.1128/jb.00434-20
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Characterization of the Conserved Regulatory Mechanism of the Escherichia coli M48 Metalloprotease BepA

Abstract: The asymmetric Gram-negative outer membrane (OM) is the first line of defence for bacteria against environmental insults and attack by antimicrobials. The key component of the OM is lipopolysaccharide, which is transported to the surface by the essential lipopolysaccharide transport (Lpt) system. Correct folding of the Lpt system component LptD is regulated by a periplasmic metalloprotease, BepA. Here we present the crystal structure of BepA from Escherichia coli, solved to a resolution of 2.18 Å, in which the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…We note that during the preparation of this manuscript, an archived preprint (35) reported determination of the E. coli BepA structure and analysis of His-246. The structure solved in that study was very similar to the structure we have reported previously and, consistent with our results, their mutational analysis of His-246 and the α9/H246 loop in that study reportedly supported the importance of these elements in the overall BepA function, although the protease activity of the His-246 mutants of BepA was not directly examined in that report.…”
Section: Discussionmentioning
confidence: 99%
“…We note that during the preparation of this manuscript, an archived preprint (35) reported determination of the E. coli BepA structure and analysis of His-246. The structure solved in that study was very similar to the structure we have reported previously and, consistent with our results, their mutational analysis of His-246 and the α9/H246 loop in that study reportedly supported the importance of these elements in the overall BepA function, although the protease activity of the His-246 mutants of BepA was not directly examined in that report.…”
Section: Discussionmentioning
confidence: 99%
“…A Dali search of the PDB with the structure of NleC (PDB id 4Q3J) revealed the E. coli BepA metalloprotease (PDB id 6SAR, [ 97 ]) as its closest, no-T3SE relative (Z-score = 5.3 and rmsd = 3.5 Å). A noticeable difference between the proteins is the distortion of a Ψ-loop β-sheet motif in the T3SE [ 98 ].…”
Section: Marginal Resemblance Of T3se Folds To Functionally Related Proteinsmentioning
confidence: 99%
“…The edge strand directly interacts with a substrate polypeptide and converts it into an extended conformation for its presentation to the active site and proteolysis. The solved structures of Escherichia coli BepA (24, 25) show that it has a β-strand (β2) that is conserved among the M48-peptidases and is located adjacent to the active site (Fig.1 A and Fig. S1), suggesting that this strand presumably acts as an edge strand.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was unexpected as it raised a question of how degradation of the normally assembling LptD intermediate can be avoided despite its interaction with the edge strand near the protease active site. In the BepA structures, the conserved His-246 residue is coordinated to a zinc ion in the active site to block the activation of a water molecule necessary for the catalysis of the proteolytic reaction (24, 25). We have recently reported that His-246 acts as a switch to regulate the proteolytic activity of BepA (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation